If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = (5x + -3)(2x + 1) Reorder the terms: y = (-3 + 5x)(2x + 1) Reorder the terms: y = (-3 + 5x)(1 + 2x) Multiply (-3 + 5x) * (1 + 2x) y = (-3(1 + 2x) + 5x * (1 + 2x)) y = ((1 * -3 + 2x * -3) + 5x * (1 + 2x)) y = ((-3 + -6x) + 5x * (1 + 2x)) y = (-3 + -6x + (1 * 5x + 2x * 5x)) y = (-3 + -6x + (5x + 10x2)) Combine like terms: -6x + 5x = -1x y = (-3 + -1x + 10x2) Solving y = -3 + -1x + 10x2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -3 + -1x + 10x2
| -6(4d+10)+7d=-3d | | 202=(4x-1)*(5x+3) | | 3(n-3)-(7-n)= | | 50.4=2.5x*(15.4+y) | | 12=7t-44 | | x+2/8=-3 | | 50.4=2.5x*(15.4+x)y | | 2y+3(y+5)= | | 50.4=2.5x*(15.4+x) | | 3x+1-2x-7=0 | | f(x)=2x^4+x^3-53x^2-14x+20 | | 10x-12=9x | | 12*k-13=39 | | 2-y=2-1 | | -5(-5+4w)=-15 | | 1=7t+8 | | 15+4k=-57 | | 2x+4+62=180 | | -20-13x=-371 | | 7+7b=35 | | -45=7-2p | | 19=23-4b | | Log(x+14)-log(x+6)=logx | | t-3=13 | | 13+7v=97 | | 3(x-7)=x-6 | | 105-3h=69 | | 6x+16=5x+9 | | 1.5(x-24)=13 | | f(-3)=6x^2-12 | | 4(3z-5)+9(5z+4)= | | 16=3d+1 |